Efecto del envase y del riego en vivero en el establecimiento de Pinus cooperi Blanco en dos condiciones de sitio - Prieto-Ruiz, José Ángel; Domínguez-Calleros, Pedro Antonio; Cornejo-Oviedo, Eladio H.; Návar-Cháidez, José de Jesús (Instituto de Ecología, A.C., 2016)
The objective was to evaluate seedling performance of Pinus cooperi Blanco planted at two contrasting field conditions: El Carmen, Durango, and Santa Lucía, Pueblo Nuevo, Dgo. The seedlings were produced under the following routines at the nursery: two sizes of container (80 cm3 and 170 cm3), and three irrigation frequencies (every 48, 96 and 168 hours). A split-split plot experimental random block design was established at the two sites. Seedlings survival, height, diameter growth, and phytomass production were evaluated during 18 months. The container of 170 cm3 had a significantly superior effect (p<0,05) on diameter growth and phytomass production, with averages of 9,26 mm and 19 ,0 g, respectively. The 96 hours irrigation frequency had a significantly superior effect (p<0,05) on diameter growth and phytomass production, with 9,17 mm and 17,9 g, respectively. It was not found a statistical significance (p>0,05) of container sizes and irrigation frequencies on seedling survival and height growth. The plantation site factor had a significance statistical (p<0,05) on seedling survival and height growth. The highest survival rate, 85,6 %, was found at El Carmen, Durango, Dgo, and the largest height growth, 18,5 cm, was recorded at Santa Lucía, Pueblo Nuevo, Dgo.